Interpretasi Tindak Tutur melalui Metakognisi pada Pidato Presiden: Kajian Kritis terhadap Pidato Kepala Negara - Nuryansyah Adijaya; M. Natsir Amir; M. Yanuardi Zain; Febriyantina Istiara (LPPM STKIP PGRI Bandar Lampung, 2025)
This study aims to explore the influence of metacognition on the comprehension of speech acts within presidential speeches. Presidential speeches are a formal mode of communication that requires the audience to grasp both the explicit and implicit meanings of the messages conveyed. In this communication process, metacognition—which involves awareness, monitoring, and regulation of cognitive processes—plays a crucial role in helping the audience identify intentions, resolve ambiguities, and enhance comprehension effectiveness. This study employs qualitative content analysis to identify the metacognitive strategies applied by listeners and to assess their impact on interpreting speech acts in presidential speeches. The findings reveal that listeners with high metacognitive awareness are better equipped to accurately and reflectively understand messages, particularly when faced with indirect speech or implicit meanings. In addition to contributing theoretically by enriching the study of the relationship between metacognition and speech acts, this research also offers practical insights for public speakers to craft more effective, persuasive, and audience-responsive speeches. These findings are expected to enhance formal communication practices and foster stronger connections between leaders and society.